Influence of the adhesive protocol on the marginal integrity of cervical composite resins - Rios Navas, Fabian Alberto (2021)
A rehabilitation option for non-carious cervical lesions is through composite resins, however, these present difficulties due to biological and clinical factors, which can affect the adhesion mechanism. The adhesives can be used under the etch and rinse protocol, as well as self-etch, the latter have simplified steps in order to reduce clinical time without affecting the quality of the restoration. Despite the development of new adhesive materials, they still have flaws. Through this systematic review, we seek to determine which adhesive protocol has a better clinical behavior compared to the marginal integrity of composite resins in non-carious cervical lesions, in order to obtain better clinical results and avoid treatment failure. Three databases were examined: PubMed, Scopus, and Web of Science, using predefined search criteria: P: Patients in need of LCNC restorations, I: Composite resins bonded with self-etch adhesives, C: Composite resins bonded with etch and rinse adhesives, O: Marginal integrity (adaptation and marginal staining). We carry out the selection of articles and the extraction of data in duplicate and independently. The process was predefined and piloted by PRISMA guidelines. Based on the evidence, we have determined the adhesive system that presents the best clinical performance in terms of staining and marginal adaptation, establishing that 2-step self-etch adhesives present the same performance as 3-step etch and rinse adhesives, however the latter deliver less staining of the restoration margins.